A Series of Suicides and Homicides by Cyanide in Türkiye: Exploring the Role of Media Reports and the Copycat Effect - Deveci, Cemyiğit; Atılgan, Mehmet (European Journal of Therapeutics, 2024)
Objectives: This paper focuses on the intentional deaths by cyanide that occurred in Turkey and aims to discuss the effect of internet and the media on these cases. Methods: Five highly circulated daily newspapers were selected and the term “siyanür”, which means “cyanide” in Turkish, were searched within their online search function between 2017-2021. A Google Trends analysis was performed with “siyanür+siyanur” as the keyword, “Turkey” as the region, and “1/1/2017-12/31/2021” as the custom time range. Results: Twenty different incidents and news reports of cyanide related suicides and/or homicides with 29 total deaths were found. In Google Trends analysis, seven out of total 8 periods of increased search interest coincided with the news reports related to cyanide deaths. Conclusions: The authors observed a surge in cyanide-related incidents following a highly publicized case in May 2019, with a peak in November 2019. The study highlights the influence of media coverage on subsequent incidents, with newspapers often using sensational headlines and providing detailed information on suicide methods. Reporting a news article on suicide requires great care and caution. Thus, the guidelines on reporting suicide related news should be implemented nationwide with a collaboration between media professionals and health-care experts.